The house of the scorpion - Farmer, Nancy, 1941- (London : Simon & Schuster, 2013)
In a future where humans despise clones, Matt enjoys special status as the young clone of El Patron, the one hundred forty-two-year-old leader of a corrupt drug empire nestled between Mexico and the United States.
6.3
5-8.
5-8
Newbery Medal/Honor, 2003
Keywords: Cloning -- Fiction; Science fiction; Cloning -- Fiction; Science fiction